2023
DOI: 10.1039/d3en00223c
|View full text |Cite
|
Sign up to set email alerts
|

Coupling effects between metal–organic framework derivatives and oxygen-deficient TiO2 nanotubes: identified charge-transfer processes and photoelectric synergistic effect

Abstract: Identified charge-transfer processes and photoelectric synergistic effect of the photoanode enhance the antibiotic wastewater treatment and free radical synergies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…First, the slope of the M–S curve for BiOCl is positive, indicating that this is an n-type semiconductor, whereas the slope of the M–S curve for Mt is negative, suggesting that Mt exhibits p-type semiconductor properties. 45 In addition, it was observed that the M–S curve of 1B/1M had an inverted “V” shape (Fig. S8†); this demonstrated that a p–n heterojunction formed between the two materials with significant proof.…”
Section: Resultsmentioning
confidence: 91%
“…First, the slope of the M–S curve for BiOCl is positive, indicating that this is an n-type semiconductor, whereas the slope of the M–S curve for Mt is negative, suggesting that Mt exhibits p-type semiconductor properties. 45 In addition, it was observed that the M–S curve of 1B/1M had an inverted “V” shape (Fig. S8†); this demonstrated that a p–n heterojunction formed between the two materials with significant proof.…”
Section: Resultsmentioning
confidence: 91%
“…Moreover, the ordered pore structure of MOFs can envelop other metal salts or organic species which could further modify MOF derivatives [26,33]. Recently, MOF derivatives have been widely used in heterogeneous catalysis, especially those using MOF derivatives as a support for metal nanoparticles [34][35][36][37][38]. Zeng et al [34] synthesized the hierarchical mesoporous CuO@NiO (M-CuO@NiO) catalyst using MOFs as the precursor.…”
Section: Introductionmentioning
confidence: 99%